Transcriptional upregulation of CXCL13 is correlated with a favorable response to immune checkpoint inhibitors in lung adenocarcinoma. (1st December 2022) - Park, Sehhoon; Cha, Hongui; Kim, Hong Sook; Lee, Boram; Kim, Soyeon; Kim, Tae Min; Jung, Hyu Ae; Sun, Jong‐Mu; Ahn, Jin Seok; Ahn, Myung‐Ju; Park, Keunchil; Park, Woong‐Yang; et al.
Abstract: Background: The chemokine CXCL13 is known to influence local anti‐tumor immunity by recruiting immune cells and forming tertiary lymphoid structures (TLS). It has been hypothesized that TLS, led by the expression of CXCL13, could be a predictive or prognostic biomarker for immunotherapy. We investigated the predictive value of CXCL13 to immune checkpoint inhibitors (ICI) in lung adenocarcinoma. Methods: We constructed an exploratory dataset ( n = 63) and a validation dataset ( n = 57) in metastatic lung adenocarcinoma patients treated with ICI. Based on the clinical response, the difference in gene expression profile, including CXCL13, was evaluated. Results: From the exploratory dataset, CXCL13 expression was significantly upregulated in the ICI responders ( p = 0.002). Survival analysis using a cut‐off value of the median expression value of CXCL13 showed prolonged progression‐free survival (PFS) ( p = 0.004) and overall survival (OS) ( p = 0.007). CXCL13 expression was correlated with other immune response genes, such as GZMA, CD8A, IFNG, PRF1, TLS‐related gene sets and its receptor, CXCR5 . Notably, subgroup analyses based on CXCL13 expression and CD8A showed that CXCL13‐ upregulated patients demonstrated comparably prolonged survival regardless of CD8A expression. In the validation dataset, CXCL13 upregulation also demonstrated a significant prolongation of both PFS ( p = 0.050) and OS ( p = 0.026). Conclusion: We observed that CXCL13 upregulation is correlated to better ICI response in lung adenocarcinoma. Our results support that CXCL13 could be an important chemokine in shaping the immunoactive tumor microenvironment which affects the anti‐tumor effect of ICI. Abstract : CXCL13 expression in lung adenocarcinoma showed predictive value to immune checkpoint inhibitor (ICI) treatment. CXCL13 expression was correlated with expression of other immune response genes. Higher median progression‐free survival and overall survival to ICI treatment are observed in CXCL13 upregulated group.